IMPLEMENTATION OF MONTESSORI METHOD IN LEARNING ACTIVITIES AT BRAINY BUNCH INTERNATIONAL ISLAMIC MONTESSORI SCHOOL MALAYSIA - Utami Utami Qonita rahmi; M Nurul Ikhsan Saleh (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The selection of effective and superior learning methods is one of the challenges in the world of education, especially in Islamic educational institutions. This study aims to analyze the Montessori method as one of the relevant methods to overcome problems in the world of education, especially related to learning methods. Metode Montessori itself has been implemented at the Brainy Bunch International Islamic Montessori School Malaysia which is also the location of this research. Researchers use qualitative research with case studies and data analyzed descriptively. The informant determination technique uses purposive sampling, where the informant involves educators in related educational institutions which include the Chief Executive Officer, Principal, Vice Principal, Teacher, and Students in the Brainy Bunch. This research found related to the internalization of Islamic values, the preparation of applied learning, the completeness of effective and inter-creative learning facilities and media, learning activities that are supported and equipped with subjects, learning focus, and learning support activities, as well as effective, descriptive and evaluative learning assessments. This research contributes to enriching scientific characteristics related to the implementation of effective Islamic Montessori methods in superior primary and secondary education learning activities.